Analisis PTSD dalam Kitab Hakim-Hakim 19:22-30 dan Relevansi Misi Perdamaian bagi Gereja Lokal: Berdasarkan Teori Judith Hermann - B Kawengian, Owen; A. Larissa, Triana Queen (Program Studi Misiologi dan Komunikasi Kristen, 2024)
This article offers an analytical study related to PTSD (Post Traumatic Stress Disorder) contained in the Book of Judges 19:22-30 concerning a concubine or servant of the Levites who was mistreated by a stranger and triggered a conflict between communities. In this case the author compares the story and its relevance for the local church situation, using Judith Hermann's thoughts on trauma and recovery. By comparing the story of the concubine of a Lewi and the situation of the local church in an effort to create peace and uncover the deeper meaning contained in the book of judges. The author shows the psycho-social situation through the eyes of the mistress of a Lewi who was a victim and a Lewi who was a witness to the incident. The research shows that this story has a traumatic impact on the victims and witnesses and this can also be a reference for local churches in addressing PTSD and to create peace in congregational life.